Information Technology Security Handbook - Sadowsky, George (Washington, DC: World Bank, 2013)
Informational and Communication Technologies (ICT) plays a fundamental role for social and economic development. Similarly, it is recognized that there cannot be an effective use of ICT in the absence of a safe and trusted ICT environment. Thus, IT security plays a prime role in helping creating the environment needed to set the ground for implementing successful national ICT plans, e-Government or e-Commerce activities, as well as sectoral projects, such as, for example, in the areas of education, health, or finance. IT security is a complex topic and evolves almost as fast as technology does. The authors provide technology-independent best practices, as well as recommendations for particular IT environments. As technology evolves, the accompanying web site (www.infodev-security.net) will provide updates as appropriate, allowing for a constant dissemination of developments in the field of IT security. The book is composed of five parts, each of which can be read independently. After an introduction to general issues of IT security, the book addresses issues relevant specifically to individuals, small and medium organizations, government, and technical administrators. Although most of the research and publications on IT security comes from developed countries, the authors have attempted to provide practical guidance applicable anywhere and to include examples from developing countries.